Energy-efficient products and competitiveness in the manufacturing sector - Giacomo Di Foggia (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Transition to a low-carbon, energy-efficient economy presents an opportunity to enhance the sustainability and competitiveness of manufacturing firms. The integration of energy-efficiency solutions into products resembles the concept of servitization that is now a lever for product competitiveness and, in turn, business performance. Based on empirical data from 293 manufacturers of electrical equipment or machinery and equipment, this paper analyzes the relation between energy-efficiency servitization capacity and performance using two structural equation models. To test the mediating role of servitization capacity, the first model uses strategic analysis of competitive structure to predict business performance, while the second model uses knowledge of the regulatory framework. Results suggest that both strategic analysis of competitive structure and knowledge of the regulatory framework positively influence performance via improving servitization capacity. With demand for new energy-efficient products expected to increase, products with a reduced energy footprint and energy-management services are needed for industrial processes to contribute to decarbonizing the economy.
Keywords: 650; innovation; energy efficiency; green economy; manufacturing; servitization